Baromagnetic Effect in Antiperovskite Mn3Ga0.95N0.94 by Neutron Powder Diffraction Analysis. Issue 19 (23rd March 2016) - Shi, Kewen; Sun, Ying; Yan, Jun; Deng, Sihao; Wang, Lei; Wu, Hui; Hu, Pengwei; Lu, Huiqing; Malik, Muhammad Imran; Huang, Qingzhen; Wang, Cong
Abstract : A baromagnetic effect in a novel tetragonal magnetic structure is introduced by vacancies in Mn3 Ga0.95 N0.94, due to the change of the Mn–Mn distance and their spin re‐orientation induced by a pressure field. This effect is proven for the first time in antiperovskite compounds by neutron powder diffraction analysis. This feature will enable wide applications in magnetoelectric devices and intelligent instruments.